THE EFFECT OF RESISTANCE TRAINING AND ANTIOXIDANT SUPPLEMENTATION WITH ASTAXANTHIN ON PLASMA MALONDIALDEHYDE (MDA) LEVELS IN ADULTS - Limyati, Yenni; Rahmia, Puteri; Hutapea, Albert Manggading (Jurnal Health Sains, 2025)
Resistance training has grown in importance for managing oxidative stress, particularly in adults, as it enhances muscle development and overall health. However, it also leads to the formation of reactive oxygen species (ROS), which can result in cellular oxidative damage and potentially hasten the aging process. This review assesses the role of astaxanthin, a powerful antioxidant, in counteracting oxidative stress during resistance training, with a focus on its effects on aging. This study employs a narrative review methodology, evaluating peer-reviewed publications from 2019 to 2024. Keywords used include "Aging," "Antioxidant," "Astaxanthin," "Oxidative Stress," and "Adults." Twenty-five articles were selected for in-depth analysis. The findings suggest that astaxanthin supplementation notably decreases oxidative stress markers, particularly plasma malondialdehyde (MDA) levels, in individuals undergoing resistance training. On a molecular level, astaxanthin activates the Nrf2 pathway, which is responsible for regulating antioxidant enzyme production and supports mitochondrial biogenesis through the PGC-1α pathway. This dual mechanism not only reduces oxidative damage but also enhances energy metabolism, helping maintain cellular function and delaying age-related decline. In conclusion, incorporating astaxanthin supplements into resistance training routines offers promising potential for reducing oxidative stress and promoting healthy aging in adults.